Three-year changes in physical activity and subsequent loss of ability to walk 400-m in older adults: The InCHIANTI study - Martinez-Gomez, David (Am J Phys Med Rehabil, 2018)
We examined the associations of maintaining or increasing physical activity (PA) over a 3-year follow-up with subsequent incident inability to complete the 400-m walk test (i.e. mobility disability) over 6 years of follow-up in older adults. This study included 421 participants aged ≥65 years. The 400-m walk test was assessed at baseline and at 3-, 6-, and 9-year follow-up. PA was self-reported through a 6-point rating scale at baseline and 3-year follow-up. Three-year cumulative PA (i.e. average at baseline and at 3-year follow-up) and its changes (i.e. from baseline to 3-year follow-up) were linked to subsequent incidence of mobility disability over 6 years of follow-up (i.e. from 3- to 9-year follow-up), after adjustment for potential covariates. After the 3-year period, incidence of mobility disability over the subsequent 6 years of follow-up occurred in 129 participants. The odds ratio (95%CI) of incident mobility disability associated with 1-category increase in cumulative PA was 0.63 (0.41–0.97, P=0.036). The odds ratio (95%CI) of incident mobility disability associated with 1-category increase in changes in PA was 0.56 (0.38–0.84, P=0.005). Hence, maintaining or increasing PA levels are associated with a reduced risk of mobility disability among older adults.